KAJIAN KESEIMBANGAN PADA PAKAIAN ADAT MATRUNA NYOMAN DAN MADAHA DESA TENGANAN PEGRINGSINGAN - I Gusti Bagus Bayu Baruna Ariesta; Nyoman Ayu Permata Dewi (Jurnal Da Moda, 2019)
Kain gringsing, aside from being used as cloth that can be used as traditional clothing, is used for daily needs as well as a means of religious ceremony for the people of Tenganan. As in Tenganan Village there is a MaterunaNyoman and Medaha tradition which is a typical education of the local village. In this study the traditional duhateruna clothes in the MaterunaNyoman and Medahaceremonies were examined in the overall balance of clothing. Unity is a state or similarity between the opposing forces and gives rise to a balanced impression visually or in intensity of work. This research was conducted to understand in more detail about the elements of beauty value formed from the balance of the overall traditional clothes of MaterunaNyoman and MedahaTengananPegringsingan Village.